2016
DOI: 10.3389/fphar.2016.00493
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Effects of Cannabidiol on Contextual Fear Memory Extinction

Abstract: Cannabidiol (CBD) has been established to have both acute and long-lasting effects to reduce fear memory expression. The long-lasting impact might be mediated by an enhancement of memory extinction or an impairment of memory reconsolidation. Here, we directly compared the effects of i.p. injections of cannabidiol (10 mg/kg) with those of the NMDA receptor antagonist MK-801 (0.1 mg/kg) and partial agonist D-cycloserine (DCS; 15 mg/kg) in order to determine the mnemonic basis of long-term fear reduction. We show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 33 publications
4
30
0
1
Order By: Relevance
“…Systemic administration of CBD given acutely before extinction has been shown to affect contextual fear extinction depending on the strength of fear conditioning beforehand. CBD impaired extinction after weak conditioning but enhanced extinction after strong conditioning (Song et al , ). However, CBD given systemically before auditory fear extinction reduced fear expression acutely without affecting extinction memory (Jurkus et al , ).…”
Section: Cbd Effects On Fear Memory Processingmentioning
confidence: 99%
“…Systemic administration of CBD given acutely before extinction has been shown to affect contextual fear extinction depending on the strength of fear conditioning beforehand. CBD impaired extinction after weak conditioning but enhanced extinction after strong conditioning (Song et al , ). However, CBD given systemically before auditory fear extinction reduced fear expression acutely without affecting extinction memory (Jurkus et al , ).…”
Section: Cbd Effects On Fear Memory Processingmentioning
confidence: 99%
“…MK-801 (Sigma-Aldrich) was diluted in sterile saline (0.1 mg/mL) and injected intraperitoneally (1 mL/kg) immediately after the reexposure session, or 30 min previously when specified (Lee et al 2006;Song et al 2016). Injections of MK-801 or vehicle were randomly distributed between animals.…”
Section: Drugsmentioning
confidence: 99%
“…No footshock was applied at either reexposure or test sessions. The aversive response (freezing) was automatically quantified during all sessions with a videotracking software (Viewpoint Life Sciences), and used as a memory index (Lee and Hynds 2013;Song et al 2016).…”
Section: Contextual Fear Conditioningmentioning
confidence: 99%
“…53 Activation of the CB 1 receptor has been implicated in the facilitatory effect of CBD on fear extinction, possibly as an indirect consequence of enhancing endocannabinoids within the brain. [54][55][56] Fear extinction is a form of inhibitory learning that suppresses learned fear and forms the theoretical basis for exposure therapy in the treatment of certain anxiety disorders. 25 Interestingly, a study in humans showed that CBD also enhanced fear extinction in healthy volunteers, 57 raising the possibility that CBD might enhance the therapeutic effects of psychological treatments.…”
Section: Cbd's Mechanism Of Action In Anxietymentioning
confidence: 99%